Zagadnienie totalitaryzmu we włoskim kręgu kulturowym. Spór o faszyzm - Fligel, Anna (Civitas. Studia z filozofii polityki, 2012)
The author aims primarily at a critical reflection on the most important threads of a debate ongoing in Italy with regard to Italian Fascism. In the Italian cultural circle, there are three phases in reflection on the issues of totalitarianism. The first is the time from the beginning of the interwar period until the end of the World War II; the development of Fascist ideology. The second phase is the period where, in fact, the question of totalitarianism is cloaked in silence; in other words, the years from the end of World War II until the nineteen seventies. When browsing through various bibliographies of Italian texts dwelling in one way or another on the issue, it becomes evident that few of them were written then. The third phase of reflection on the issue of totalitarianism is the period from the nineteen seventies to the present day.